Delivering Islamic Studies and Teaching Diversity in Southern Thai Islamic Schools - Raihani, Raihani; Karim, Promadi; M. Asyari, Sopyan; Mahnun, Nunu (Al-Jamiah Research Centre, 2016)
Teaching religious and cultural diversities would possibly be one of the greatest challenges to teachers of Islamic in Southern Thai Islamic schools due to the strong Islamic ideology they hold, lack of proper training for their professional growth, and the ongoing ethno-political conflict in the area. This paper explores how such a challenge has been faced. It particularly describes the teaching process of Islamic studies in Thai Islamic schools and explores opportunities within it for promoting religious and cultural diversities. We also look into possible opportunities for Islamic teachers to teach and students to learn about the diverse reality of society. We found that the deliveries of Islamic fell squarely within the concept of teaching into religion using a heavy confessional approach. Indoctrination with a little encouragement of critical thinking was common in Islamic classes. The presentation of other faiths and cultures was designed to explore their weaknesses and fallacies from a single believed-Islamic perspective.[Pengajaran keragaman budaya dan agama merupakan sebuah tantangan besar bagi guru pendidikan keislaman pada sekolah di Thailand Selatan, seiring dengan pemahaman keislaman mereka yang kuat, kesenjangan tingkat perkembangan profesionalitas, dan konflik politik etnik di daerah tersebut. Tulisan ini mengetengahkan persoalan yang mereka hadapi, khususnya deskripsi proses pengajaran studi keislaman di sekolah Islam lokal dan peluang dalam promosi keragaman budaya dan agama. Tulisan ini juga melihat kemungkinan peluang bagi guru agama Islam dan anak didiknya untuk saling belajar dari realitas keragaman dalam masyarakat. Kami menemukan bahwa menyampaikan pengetahuan keislaman harus tepat dengan konsep pengajaran bagi pemeluk agamanya menggunakan pendekatan keyakinan yang lurus. Indoktrinasi dengan sedikit dorongan pemikiran kritis merupakan kewajaran dalam kelas agama. Presentasi agama dan budaya lain didesain untuk eksplorasi kekurangan dan kesalahan dari perspektif yang monolitik.]